2023
DOI: 10.3390/nu15061428
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Nutritional Intake Assessment, and Perceptions about Diet for Health and Performance: An Exploratory Study for Senior Futsal Players

Abstract: This study aims to assess the body composition and nutritional intake of senior male futsal players from the II Futsal Division—Azores Series and explore their individual viewpoints regarding the benefits and barriers of healthy eating and performance. Two groups were identified: those who only completed the sociodemographic questionnaire and the anthropometric data (Group 1, n = 48), and those who additionally had their food intake assessed using three 24-h dietary recalls and were interviewed (Group 2, n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Further research reinforces the link between nutritional knowledge and athletic performance. Brum, Franchini & Moura (2023) identified a connection between futsal players’ dissatisfaction with their performance and their deviation from healthy eating habits. Similarly, Finamore et al (2022) found that non-professional athletes often lack adequate nutritional knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…Further research reinforces the link between nutritional knowledge and athletic performance. Brum, Franchini & Moura (2023) identified a connection between futsal players’ dissatisfaction with their performance and their deviation from healthy eating habits. Similarly, Finamore et al (2022) found that non-professional athletes often lack adequate nutritional knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…Given the nature of the game, it is crucial to ensure sufficient calories to balance energy expenditure to optimize performance through nutrition [14], and to maintain immune and metabolic functions [37]. Due to the high-intensity effort, the nutritional requirements for futsal players appear to be similar to other indoor team sports such as handball, basketball, and volleyball [14,38]. Energy expenditure is related to the typical specific actions of futsal (e.g., acceleration, deceleration, sprinting, changes of direction, and jumping [5]) and several other factors, such as the body type of the players and the position occupied during the game [1,39].…”
Section: Discussionmentioning
confidence: 99%